Fatores de risco para disfunção e para não função primária do fígado transplantado em um contexto brasileiro - Márcia Eller Miranda Salviano (2020)
Early graft dysfunction is described as initial malfunction, marginal function or delayed function, and it affects between 7% and 27% of liver transplant patients. The primary nonfunction is graft loss, and it affects between 1.4% and 8.4% of this population. The present study was conducted to analyze risk factors for dysfunction and non-primary function of transplanted livers. Donor, graft, patient, and transplant logistics factors were researched. This is an epidemiological study, with a historical cohort conducted with 180 medical records of transplanted patients admitted to the Intensive Care Unit, whose donors were brain dead. All transplants were performed at the Hospital das Clínicas, Federal University of Minas Gerais, Belo Horizonte, Brazil, between 2012 and 2018. Descriptive, bivariate, and multivariate statistical analyzes were performed using the Kaplan-Meier method and the Log-rank test. Association between risk factors and outcomes was assessed by Cox regression and the Backward selection process, adjusted by the Hazard ratio. The liver receptors were mostly white males with an average age of 52.1 years. Transplant indications were: alcoholic disease, 31.7%; metabolic disease and viral hepatitis, 26.1%; tumor, 22.2%; cholestatic disease, 17.8% and vascular disease, 2.8%. Body Mass Index equal to or greater than 30 kg / m² occurred 3.9%. The average score for the Model for End-Stage Liver Disease was 23, and the mean serum creatinine was 1.35mg / dl. Regarding donors, the average age was 37.6 years, with 39.4% being female. The causes of brain death were stroke in 86 (47.8%), head injury in 77 (42.8%), and for other causes in 17 (9.4%). Aspartate aminotransferase was, on average, 77.20 UI/L. Alanine aminotransferase was, on average, 60.42 UI/L. Serum sodium > 160 mmol/l occurred in 18.6%, and the mean Gamaglutamiltransferase was 77 IU / L. The average Donor Risk Index was 1.476. As for the graft, it was found that its origin was local in 37.8%; regional, in 56.7%; and national, in 5.5% of cases. The cold ischemia time (> 10 hours) occurred in 58 (32.2%), the warm ischemia time (> 60 minutes) occurred in 14 (9.9%) of the transplants. The average time of the recipient's surgery was 6.1 hours, who received 4 U of platelets on average. 5 (2.8%) received fresh frozen plasma > 30 U. The average Balance of risk was 10. The normal clinical evolution occurred in 66 (36.7%) of the patients. Early graft dysfunction occurred in 104 (57.8%), and primary non-function in 10 (5.5%). The risk factors for early graft dysfunction were the female donor, the graft warm ischemia time greater than 60 minutes, and the11 consumption of fresh frozen plasma > 30 U by the recipient. The risk factor for primary nonfunction was the volume of platelets consumed by the recipient. The control of these risk factors contributes to the adequate function of the liver after transplantation and to improve grafts and patient’s survival